Imposing Corporate Death Penalty in Indonesia: A Discourse on Penalisation, Corporate Culture, and Deferred Prosecution Agreement - Zakaria, Alfons; Madjid, Abdul; Sugiri, Bambang; Sihabudin, Sihabudin; Mohd Hassan, Fareed (Udayana Journal of Law and Culture; Vol 8 No 2 (2024)DO - 10.24843/UJLC.2024.v08.i02.p04, 2024)
The Indonesian Penal Code 2023 regulates corporate criminal liability. It covers various issues, including the actions of a corporation that amount to corporate crimes, the conditions under which a corporation can be held criminally responsible, who can be held accountable, and the types of criminal sanctions imposed on corporations. The primary criminal sanction is the imposition of fines. However, several types of additional punishments may also be imposed, including dissolution of the corporation or, in other words, the “corporate death penalty”, which leads to a permanent termination of the corporation's operations, loss of jobs for employees, termination of production, and stoppage of tax payments to the government. Thus, if imposed without caution, corporate death penalty will negatively impact the state and society. This article analyses the effect of corporate death penalty on the society and highlights the need for judges to exercise caution before dissolving a corporation. The study applies normative legal research with the statutory and comparative approach. Primary and secondary legal materials were analysed. This article argues against the imposition of corporate death penalty in Indonesia for three reasons. First, Indonesia does not have sentencing guidelines for corporations. Second, Indonesia has not developed a Deferred Prosecution Agreement (DPA) mechanism yet, which is an obstacle to developing a better corporate culture . Third, corporate death penalty has harmful impacts on a country's economy and public welfare; among others, it increases the unemployment rate, which impacts social life.